Flexible super-structure surface film and preparation method and application thereof

By mixing inorganic nanoparticles with transparent organic polymers and preparing them by calendering process, the complex and rigid problems of traditional hard supersurface preparation are solved, and the preparation of flexible supersurface films is realized, with excellent mechanical properties and a wide range of Application prospects.

CN119409999APending Publication Date: 2025-02-11ZHEJIANG SHENGYI OPTICAL SENSING TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411650770.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Traditional hard superstructure surfaces have problems such as complex preparation and high cost, rigid properties, fixed optical properties and mechanical properties, which limit their application in flexible electronics, wearable devices and other fields.

Method used

By mixing inorganic nanoparticles with transparent organic polymers, a flexible supersurface film is prepared by calendering process to achieve flexible regulation of optical parameters, structure and size.

Benefits of technology

The prepared flexible supersurface film has excellent mechanical strength and flexibility, is easier to bend or adhere to curved surfaces, has high durability and reliability, and is suitable for flexible display screens and flexible sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409999A_ABST
    Figure CN119409999A_ABST
Patent Text Reader

Abstract

The invention relates to a flexible super-structure surface film and a preparation method and application thereof. The preparation method of the flexible super-structure surface film comprises the following steps: mixing inorganic nanoparticles and a transparent organic polymer to form slurry; and placing the slurry on the surface of a substrate, calendaring the surface, far away from the substrate, of the slurry, and separating the slurry from the substrate after curing to prepare the flexible super-structure surface film. According to the preparation method, the optical parameters of the flexible super-structure surface film can be flexibly adjusted, the process is simple, the processing time and cost can be reduced, and the prepared flexible super-structure surface film is easier to bend or attach to a curved surface and has wide application prospects in the fields of flexible display screens, flexible sensors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optical technology, and in particular to a flexible metasurface film and a preparation method and application thereof. Background Art

[0002] In the field of optics and materials, metasurfaces are an important innovative technology that achieves precise control of the amplitude, phase, and polarization state of light through nanoscale structural design. The precise control of the phase of light waves by metasurfaces can be applied in the design of ultra-thin lenses to focus and image incident light waves at the nanoscale. They have the characteristics of light weight, thin thickness, and high resolution. For example, in terms of amplitude modulation, metasurfaces can be used to manufacture high-performance optical filters and reflectors, which can selectively filter light of specific wavelengths and improve the optical performance of the system; in terms of optical polarization modulation, the flexible control of incident light by metasurfaces can be used to manufacture polarization converters and polarization separators; in optical communication systems, the efficiency and stability of signal transmission can be improved, and in display technology, it can be used to enhance the contrast and clarity of images.

[0003] Traditional metasurface technologies mostly use hard materials, such as metals such as gold and silver, semiconductor materials such as silicon and gallium arsenide, or high-refractive-index metal oxide materials such as titanium dioxide. However, these hard metasurfaces have major disadvantages such as complex and expensive preparation, rigid characteristics, fixed optical properties, and fragile mechanical properties. Specifically, the preparation of metal and semiconductor nanostructures usually requires the use of high-precision and high-cost processing technologies such as electron beam lithography (EBL) and reactive ion etching (RIE). These processes are not only time-consuming, but also have strict requirements on equipment and environment, resulting in high costs for large-scale production. In addition, the lack of flexibility of hard metasurface materials limits their use in applications that require flexibility and shape adaptability, such as flexible electronics and wearable devices. For example, hard materials cannot be easily bent or attached to curved surfaces, which limits their application in flexible displays, flexible sensors, and other fields. In addition, hard materials have low mechanical strength at the nanoscale and are easily damaged by external forces, which reduces the durability and reliability of traditional metasurfaces in practical applications.

[0004] In response to these problems, researchers have proposed some improvement plans. For example, by introducing a polymer matrix, a flexible polymer-metal nanocomposite metasurface has been developed. Although this solution improves the flexibility of the metasurface to a certain extent, it still faces problems such as limited optical performance, material compatibility issues, and limited control dimensions. In addition, the interface between the polymer and the metal nanostructure is weak, which is prone to separation or performance degradation during use, affecting the long-term stability and reliability of the device. Although the introduction of polymers improves flexibility, the control of the optical properties of the material mainly depends on the design and distribution of the nanostructure, and the control dimension is relatively limited. Summary of the invention

[0005] Based on this, it is necessary to provide a flexible metasurface film and its preparation method and application to address the above problems; the preparation method can not only flexibly adjust the optical parameters of the flexible metasurface film, but also has a simple process, which is conducive to reducing processing time and cost. The prepared flexible metasurface film is easier to bend or adhere to a curved surface, and has broad application prospects in flexible display screens, flexible sensors and other fields.

[0006] A method for preparing a flexible metasurface film comprises the following steps:

[0007] mixing the inorganic nanoparticles with the transparent organic polymer to form a slurry;

[0008] The slurry is placed on the surface of a substrate to form a slurry layer, a surface of the slurry layer away from the substrate is subjected to calendering treatment, and after solidification, the surface is separated from the substrate to obtain a flexible meta-structure surface film.

[0009] In one embodiment, the inorganic nanoparticles are selected from cesium tungsten bronze, mixed particles of cesium tungsten bronze and silicon dioxide, mixed particles of cesium tungsten bronze and titanium dioxide, or mixed particles of cesium tungsten bronze, silicon dioxide, and titanium dioxide.

[0010] In one embodiment, the particle size of the cesium tungsten bronze is 20nm-100nm.

[0011] In one embodiment, the transparent organic polymer is selected from at least one of polymethyl methacrylate and polydimethylsiloxane.

[0012] In one of the embodiments, in the slurry, the volume percentage of the inorganic nanoparticles is 3%-10%.

[0013] In one embodiment, after the calendering process, a pyramid structure is formed on the surface of the slurry layer away from the substrate.

[0014] In one of the embodiments, the period of the pyramid structure is 1 μm-5 μm, and in the pyramid structure, the base size of any pyramid is 100 nm-300 nm, and the height is 1 μm-5 μm.

[0015] A flexible metasurface film prepared by the preparation method as described above, wherein the flexible metasurface film comprises a transparent organic polymer and inorganic nanoparticles distributed in the transparent organic polymer.

[0016] In one of the embodiments, any surface of the flexible metasurface film has a pyramid structure.

[0017] An optical device comprises the flexible metasurface film as described above.

[0018] The preparation method described in the present invention performs optical design by mixing inorganic nanoparticles with transparent organic polymers as a whole. On the one hand, it has higher flexibility and can flexibly control the optical parameters, structure and size of the flexible metasurface film, which can make it easier to achieve the expected results, and can reduce the computing resources consumed in the optical design and improve efficiency. On the other hand, the calendering process is used to prepare the optical metasurface, and a complex structure can be prepared in a single processing, avoiding the use of high-demand processing methods such as lithography and etching, reducing processing time and cost, and reducing pollution caused during the processing.

[0019] Therefore, the flexible metasurface film prepared by the preparation method provided by the present invention has excellent mechanical strength and flexibility, is easier to bend or adhere to a curved surface, and has high durability and reliability, and has broad application prospects in the fields of flexible display screens, flexible sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 The present invention is a flow chart of a method for preparing a flexible metasurface film according to an embodiment of the present invention.

[0022] Among them, 10. Flexible metasurface film; 101. Inorganic nanoparticles; 102. Transparent organic polymer; 20. Substrate. DETAILED DESCRIPTION

[0023] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0025] Combination Figure 1 As shown, a method for preparing a flexible metasurface film 10 provided by the present invention comprises the following steps:

[0026] S1, mixing the inorganic nanoparticles 101 and the transparent organic polymer 102 to form a slurry;

[0027] S2, placing the slurry on the surface of the substrate 20 to form a slurry layer, performing calendering treatment on the surface of the slurry layer away from the substrate 20, and separating it from the substrate 20 after curing to obtain a flexible meta-structured surface film 10.

[0028] In step S1, the inorganic nanoparticles 101 and the transparent organic polymer 102 are mixed as a whole for optical design, so that the preparation method described in the present invention has higher flexibility and can flexibly control the optical parameters, structure and size of the flexible metasurface film 10, which can make it easier to achieve the expected results, and can reduce the computing resources consumed in the optical design and improve efficiency.

[0029] It can be understood that, as described in the present invention, "mixing" refers to the physical mixing of the inorganic nanoparticles 101 and the transparent organic polymer 102 without causing chemical changes, and the present invention does not limit the order of "mixing", and the inorganic nanoparticles 101 can be added to the transparent organic polymer 102 for mixing, or the transparent organic polymer 102 can be added to the inorganic nanoparticles 101 for mixing. Both mixing methods can obtain the slurry described in the present invention.

[0030] Specifically, by selecting the specific material, size and other physicochemical parameters of the inorganic nanoparticles 101 and the transparent organic polymer 102, and extracting optical parameters (such as refractive index, extinction coefficient, etc.) based on Maxwell's equations and equivalent dielectric theory, the optical properties of the flexible metasurface film 10, such as transmittance, absorption rate and scattering characteristics, can be flexibly adjusted.

[0031] In one embodiment of the present invention, the inorganic nanoparticles 101 are selected from cesium tungsten bronze (Cs xWO3, wherein x=0-0.33), mixed particles of cesium tungsten bronze and silicon dioxide (SiO2), mixed particles of cesium tungsten bronze and titanium dioxide (TiO2), or mixed particles of cesium tungsten bronze, silicon dioxide and titanium dioxide.

[0032] It is understandable that, as described in the present invention, the inorganic nanoparticles 101 may refer to single particles, such as cesium tungsten bronze, or mixed particles, such as mixed particles of cesium tungsten bronze and silicon dioxide, mixed particles of cesium tungsten bronze and titanium dioxide, or mixed particles of cesium tungsten bronze and silicon dioxide, titanium dioxide. In the mixed particles, the particle sizes of cesium tungsten bronze, silicon dioxide, and titanium dioxide may be the same or different, and the present invention does not limit this.

[0033] In one embodiment of the present invention, the inorganic nanoparticles 101 are preferably cesium tungsten bronze. Further, the particle size of the cesium tungsten bronze is preferably 20nm-100nm, including but not limited to any one point value of 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, and 100nm, or a range value composed of any two point values, wherein the range value composed of any two point values ​​includes but is not limited to 20nm-50nm, 30nm-60nm, 40-80nmnm, 50nm-90nm, and 60nm-100nm.

[0034] It is understandable that in the present invention, inorganic nanoparticles 101 of a specific particle size can be directly used as a preparation raw material, or the inorganic nanoparticles 101 raw material can be pretreated before the step of mixing the inorganic nanoparticles 101 with the transparent organic polymer 102 so that the inorganic nanoparticles 101 reach a desired size. Specifically, the present invention does not limit the pretreatment method of the inorganic nanoparticle 101 raw material, including but not limited to processes such as mechanical polishing.

[0035] In one embodiment of the present invention, the transparent organic polymer 102 is selected from at least one of polymethyl methacrylate (PMMA) and polydimethylsiloxane (PDMS).

[0036] It is understandable that, as described in the present invention, the transparent organic polymer 102 can be a single-component polymer, such as polymethyl methacrylate or polydimethylsiloxane, or a multi-component mixed polymer, such as a mixed polymer of polymethyl methacrylate and polydimethylsiloxane, and the present invention is not limited to this.

[0037] In one embodiment of the present invention, the slurry is preferably a mixture of cesium tungsten bronze and polymethyl methacrylate. Furthermore, in the slurry, cesium tungsten bronze is evenly distributed in polymethyl methacrylate to form a relatively uniform mixture.

[0038] It should be noted that the present invention does not limit the mixing method of the inorganic nanoparticles 101 and the transparent organic polymer 102 , and a mechanical stirring mixing method, such as magnetic stirring, or an ultrasonic oscillation mixing method may be used.

[0039] By adjusting the volume percentage of the inorganic nanoparticles 101 in the slurry, it is beneficial to optimize the concentration of the inorganic nanoparticles 101 in the slurry, thereby flexibly adjusting the optical properties of the flexible metasurface film 10 .

[0040] In one embodiment of the present invention, in the slurry, the volume percentage of the inorganic nanoparticles 101 is preferably 3%-10%, including but not limited to any one point value of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range value composed of any two point values, wherein the range value composed of any two point values ​​includes but is not limited to 3%-7%, 4%-8%, 5%-9%, 6%-10%, 5%-10%, 4%-10%.

[0041] In step S2, a calendering process is used to prepare the optical metasurface, and a complex structure can be prepared in a single process, avoiding the use of high-demand processing methods such as lithography and etching, reducing processing time and cost, and reducing pollution caused during the processing.

[0042] It should be noted that the present invention does not limit the specific process of placing the slurry on the surface of the substrate 20, including but not limited to coating, spraying, scraping, spin coating, etc. The present invention does not limit the material of the substrate 20, and a substrate commonly used in existing preparation processes can be used, such as a glass plate.

[0043] It is understandable that after the slurry is placed on the surface of the substrate 20 to form a slurry layer, there is one side in the slurry layer that contacts the substrate 20. As described in the present invention, the surface of the slurry layer away from the substrate 20 is subjected to calendering. In other words, the surface opposite to the surface of the slurry layer that contacts the substrate 20 is subjected to calendering. The present invention does not limit the specific method of calendering. Furthermore, a mold can be used for calendering, wherein the mold preferably has the characteristics of easy demoulding, anti-adhesion, wear resistance and high temperature resistance. The metasurface structure of the flexible metasurface film 10 depends on the mold shape used in the present invention. Therefore, different mold shapes can be designed according to the properties of light refraction, dispersion, etc., and metasurfaces with different complex structures can be prepared.

[0044] In one embodiment of the present invention, after the calendering treatment, the slurry layer is cured to form a pyramid structure on the surface of the slurry layer away from the substrate 20, wherein the curing method is selected from light curing or thermal curing. It is understood that, as described in the present invention, the pyramid structure includes a plurality of tetrahedrons that are narrow at the top and wide at the bottom arranged in an array.

[0045] Further, in one embodiment of the present invention, the period of the pyramid structure is preferably 1μm-5μm, including but not limited to any one point value of 1μm, 2μm, 3μm, 4μm, and 5μm, or a range value consisting of any two point values, wherein the range value consisting of any two point values ​​includes but is not limited to 1μm-3μm, 2μm-4μm, and 1μm-5μm; in the pyramid structure, the bottom size of any pyramid is preferably 100nm-300nm, including but not limited to any one point value of 100nm, 150nm, 200nm, 250nm, and 300nm, or a range value consisting of any two point values; the height of any pyramid is preferably 1μm-5μm, including but not limited to any one point value of 1μm, 2μm, 3μm, 4μm, and 5μm, or a range value consisting of any two point values.

[0046] It should be noted that, considering that the curing temperature depends on the specific material of the transparent organic polymer 102, the present invention does not limit the specific conditions for curing, and those skilled in the art can select appropriate curing temperature and curing time according to the transparent organic polymer 102 used. For example: when polymethyl methacrylate is used as the transparent organic polymer 102, the curing temperature is 30°C-40°C, and the curing time is 3h-6h; when polydimethylsiloxane is used as the transparent organic polymer 102, the curing temperature is 30°C-60°C, and the curing time is 3h-6h.

[0047] The present invention provides a flexible metasurface film prepared by the preparation method as described above, wherein the flexible metasurface film comprises a transparent organic polymer and inorganic nanoparticles distributed in the transparent organic polymer.

[0048] The flexible metasurface film prepared by the preparation method provided by the present invention has excellent mechanical strength and flexibility, is easier to bend or adhere to a curved surface, and has high durability and reliability. It has broad application prospects in the fields of flexible display screens, flexible sensors, etc.

[0049] In one embodiment of the present invention, the transmittance of the flexible metasurface film to visible light is greater than 30%, the absorptivity to near-infrared light is greater than 60%, and the oscillation (scattering fluctuation) of the transmittance within the two wavelength bands of visible light and near-infrared light is less than 10%.

[0050] In one embodiment of the present invention, the flexible metasurface film includes polymethyl methacrylate and cesium tungsten bronze distributed in the polymethyl methacrylate.

[0051] In one embodiment of the present invention, the flexible metasurface film includes polydimethylsiloxane and cesium tungsten bronze distributed in the polydimethylsiloxane.

[0052] In one embodiment of the present invention, the flexible metasurface film includes polymethyl methacrylate, and cesium tungsten bronze, silicon dioxide and titanium dioxide distributed in the polymethyl methacrylate.

[0053] In one embodiment of the present invention, the flexible metasurface film includes polymethyl methacrylate, and cesium tungsten bronze and silicon dioxide distributed in the polymethyl methacrylate.

[0054] In one embodiment of the present invention, the flexible metasurface film includes polymethyl methacrylate, and cesium tungsten bronze and titanium dioxide distributed in the polymethyl methacrylate.

[0055] In one embodiment of the present invention, any surface of the flexible metasurface film has a pyramid structure. It is understood that the present invention does not limit the opposite surface of the flexible metasurface film having the pyramid structure surface, and it can be an untreated smooth surface.

[0056] The present invention also provides an optical device, including the flexible metasurface film as described above. It can be understood that the optical device includes but is not limited to flexible display screens and flexible sensors. Furthermore, the flexible metasurface film described in the present invention is particularly suitable for flexible display screens and flexible sensors.

[0057] The flexible metasurface film and its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0058] Example 1

[0059] 5 g of cesium tungsten bronze was mixed with 95 g of polymethyl methacrylate, and ultrasonically stirred to form a uniform slurry.

[0060] The prepared slurry is spin-coated on the surface of a glass plate, and then a mold is used to emboss a metasurface structure on the surface of the spin-coated slurry. The slurry is then placed in an oven and cured at 35°C for 4 hours. Finally, the cured material is peeled off from the glass surface to obtain a flexible metasurface film.

[0061] Example 2

[0062] 6 g of cesium tungsten bronze was mixed with 94 g of polymethyl methacrylate, and ultrasonic agitation was used to form a uniform slurry.

[0063] The prepared slurry is spin-coated on the surface of a glass plate, and then a mold is used to emboss a metasurface structure on the surface of the spin-coated slurry. The slurry is then placed in an oven and cured at 35°C for 4 hours. Finally, the cured material is peeled off from the glass surface to obtain a flexible metasurface film.

[0064] Example 3

[0065] 7 g of cesium tungsten bronze was mixed with 93 g of polymethyl methacrylate, and ultrasonic agitation was used to form a uniform slurry.

[0066] The prepared slurry is spin-coated on the surface of a glass plate, and then a mold is used to emboss a metasurface structure on the surface of the spin-coated slurry. The slurry is then placed in an oven and cured at 35°C for 4 hours. Finally, the cured material is peeled off from the glass surface to obtain a flexible metasurface film.

[0067] Example 4

[0068] 4 g of cesium tungsten bronze, 1 g of silicon dioxide, 1 g of titanium dioxide and 95 g of polydimethylsiloxane were mixed and stirred by ultrasonic vibration to form a uniform slurry.

[0069] The prepared slurry is spin-coated on the surface of a glass plate, and then a mold is used to emboss a metasurface structure on the surface of the spin-coated slurry. The slurry is then placed in an oven and cured at 60°C for 2 hours. Finally, the cured material is peeled off from the glass surface to obtain a flexible metasurface film.

[0070] The performance of the flexible metasurface films prepared in Examples 1-4 was tested, and the results are shown in Table 1.

[0071] Table 1

[0072]

[0073] As can be seen from Table 1, the flexible metasurface film prepared according to the preparation method provided by the present invention has flexible optical properties and excellent flexibility, and can be applied to flexible display screens, flexible sensors and other fields.

[0074] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a flexible metasurface film, characterized in that: The steps include: mixing the inorganic nanoparticles with the transparent organic polymer to form a slurry; The slurry is placed on the surface of a substrate to form a slurry layer, a surface of the slurry layer away from the substrate is subjected to calendering treatment, and after solidification, the surface is separated from the substrate to obtain a flexible meta-structure surface film.

2. The method for preparing a flexible metasurface film according to claim 1, characterized in that: The inorganic nanoparticles are selected from cesium tungsten bronze, mixed particles of cesium tungsten bronze and silicon dioxide, mixed particles of cesium tungsten bronze and titanium dioxide, or mixed particles of cesium tungsten bronze, silicon dioxide and titanium dioxide.

3. The method for preparing the flexible metasurface film according to claim 2, characterized in that: The particle size of the cesium tungsten bronze is 20nm-100nm.

4. The method for preparing a flexible metasurface film according to claim 1, characterized in that: The transparent organic polymer is selected from at least one of polymethyl methacrylate and polydimethylsiloxane.

5. The method for preparing a flexible metasurface film according to claim 1, characterized in that: In the slurry, the volume percentage of the inorganic nanoparticles is 3%-10%.

6. The method for preparing a flexible metasurface film according to claim 1, characterized in that: After the calendering treatment, a pyramid structure is formed on the surface of the slurry layer away from the substrate.

7. The method for preparing a flexible metasurface film according to claim 6, characterized in that: The period of the pyramid structure is 1 μm-5 μm. In the pyramid structure, the bottom size of any pyramid is 100 nm-300 nm, and the height is 1 μm-5 μm.

8. A flexible metasurface film obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The flexible metasurface film comprises a transparent organic polymer and inorganic nanoparticles distributed in the transparent organic polymer.

9. The flexible metasurface film according to claim 8, characterized in that: Any surface of the flexible metasurface film has a pyramid structure.

10. An optical device, characterized in that: Comprising the flexible metasurface film as described in claim 8 or 9.